Dental And Oral Health Of Students With Intellectual Disabilities - Sandy Christiono; Muhammad Dian Firdausy; Grahita Aditya; Budi Suhartono; Erwid Fatchur Rahman; Nira Ardlina; Adinda Lintang Pambayun; Amara Danish Clarasya (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Dental and oral health refers to the condition of the oral cavity and periodontal tissues being free from disease and pain. Optimal function of these structures indicates good oral health. Dental and oral health status can be expressed by the prevalence of dental caries and periodontal disease, assessed through indices such as def-t/DMF-T, OHI-S, and Gingival Index. This study aimed to determine the levels of def-t/DMF-T, OHI-S, and Gingival Index, and to describe the overall dental and oral health status among students with intellectual disabilities at Grobogan State Special SchoolMethod: This study employed a descriptive observational design with a non-experimental, cross-sectional approach to describe existing conditions through direct observation. A total of 52 students with intellectual disabilities were included using a total sampling technique.Result: DMF-T/def-t examination showed unsatisfactory findings, with the highest proportion of respondents categorized as very high (30.77%) and high (21.15%). The OHI-S examination indicated a moderate level, with most respondents (44.23%) falling within this category. The Gingival Index revealed generally good results, with the largest proportion categorized as normal (46.15%).Conclusion: Highest percentages of OHI-S and Gingival Index were found among students with moderate physical intellectual disabilities, while the highest def-t/DMF-T scores (very high category) were found among those with sensory intellectual disabilities